REGIONAL EFFECTS OF MONETARY POLICY IN CHINA: THE ROLE OF SPILLOVER EFFECTS - Guo Xiaohui,; Tajul Ariffin Masron, (Asian Academy of Management Journal, 2014)
This paper uses Structural Vector Autoregressive (SVAR) method to measure the regional effects of monetary policy in China during 1978–2011. The results provide evidence of different regional responses of real variables to monetary policy shocks. This paper proves that M2 is a better monetary policy indicator. We also find that when examining the regional effects of monetary policy in China, the spillover effects among regions are very important in the short run. In the long run, the influence of deposits transfer among regions is much bigger than that of the spillover effects.